ANALISIS RASIO FINAL GEAR DAN KEMIRINGAN JALAN TERHADAP DAYA, EFISIENSI MEKANIS, WAKTU AKSELERASI DAN SPECIFIC FUEL CONSUMPTION (SFC) PADA MOTOR 110 INJEKSI: ANALYSIS OF FINAL GEAR RATIO AND ROAD SLOPE ON POWER, MECHANICAL EFFICIENCY, ACCELERATION TIME AND SPECIFIC FUEL CONSUMPTION (SFC) IN 110 INJECTION MOTOR - Iqbaal Fawwaz Thoriq Fadhlullah (Jurnal Teknik Mesin, 2022)
The community perceives that vehicles used in daily activities, especially when carrying heavy loads such as going uphill or transporting goods, experience a lack of power and torque. The objective of this study is to determine the results of calculations and experiments on power, mechanical efficiency, acceleration time, and Specific Fuel Consumption (SFC) between using standard factory gears and modified gears. In the power test, using gear 38 resulted in the highest power output of 8.85 hp at 7500 rpm. Regarding mechanical efficiency, gear 38 achieved the highest value of 0.9987 at 6500 rpm. As for acceleration time, the steeper the road gradient, the lower the maximum achievable speed. Moreover, in terms of SFC, particularly in the test involving road gradient, the most fuel-efficient result was obtained at a 5° gradient using gear 40 with an SFC value of 0.04127 Kg/Hp.hour at 6000 rpm, while the highest fuel consumption was recorded at a 30° gradient using gear 38, with an SFC value of 0.1158 Kg/Hp.hour at 8000 rpm